Social influences on Singapore print and electronic news journalists' ethical decision making. - Chang, May Choon. (2009)
This study explores the impact of personal and external influences on ethical decisions of news journalists in Singapore. Nine proposed social influences were investigated, including individual, small group, organisation, competition, profession, source, audience, law and government. The two-tier study, comprising a survey and in-depth interviews, was conducted to explore whether external factors or personal values dictate over a journalist’s ethical decision. There is no conclusive evidence to support significant differences between the two variables, but a hierarchy of social influences could be established. It was found that journalists generally placed the highest regard for their sources, followed by journalistic professions, and their personal values. The newsroom editor and the government also emerged as strong factors of influence for ethical behaviour.